Migration mechanism of carbon nanotubes and matching viscosity-dependent morphology in Co-continuous Poly(lactic acid)/Poly(ε-caprolactone) blend: Towards electromagnetic shielding enhancement. (14th June 2022) - Tao, Jun-Ru; Yang, Dian; Yang, Yi; He, Qian-Ming; Fei, Bin; Wang, Ming
Abstract: Selective distribution of carbon nanotubes and morphology of conductive polymer composites were very important factors to their electrical conductivity and electromagnetic waves (EMW) shielding performance. Herein, the migration behavior of carbon nanotubes (CNTs) in co-continuous poly(lactic acid)/poly(ε-caprolactone) (PLA/PCL) blend was investigated via pre-compounding CNTs in one phase and controlling the mixing time. Because of the higher interaction between CNTs and PCL phase, the migration of CNTs happened from PLA phase to PCL phase when CNTs were pre-mixed with PLA. Due to the viscosity enhancement of pre-compounding PCL/CNT and PLA/CNT, the matching viscosity-dependent morphology was obvious in the composites with different mixing sequences. The better viscosity matching of two polymer phases resulted in the smaller size of two phases, which had more interfaces to enhance microwave attenuation. The effect of CNTs migration and mixing rates on morphological size and EMW shielding performance of the composites were also evaluated. Specifically, the composites with pre-mixing PCL/CNT and then PLA at low shear stress exhibited the smaller size of phases and higher EMW shielding effectiveness (SE) values because of higher interfacial polarization and higher multiple reflection/scattering. Graphical abstract: Image 1 Highlights: Carbon nanotubes prefer to disperse in PCL phase in all the composites. Migration of CNTs is the thermodynamic and kinetic behavior. Interfacial driving-separating-dividing-coalescing is repeated to migrate CNTs. Matching viscosity-dependent morphology is found in the composites. Smaller size of phases lead to more interfaces and enhance EMW shielding.